Effect of Electromagnetic Fields on Microbial Activity of a Bio-Fertilizer - Zuñiga, Orlando; Jiménez, Cristian; Benavides, Jhony; Torres González, Celina (Revista de Ciencias, 2016)
The level of microbial activity was evaluated in an organic substrate and over soil samples from the “El Limonar” county (Dagua, Valle del Cauca) to which it was applied the commercial bio-fertilizer Multibiol electromagnetically stimulated. Phase i of the experiment was conducted to determinate the best times of exposure and electromagnetic induction on the bio-fertilizaer applied to samples of an organic substrate (chicken manure).